The Succession of Upper Eocene- Upper Miocene Limestone Growth and Corresponding Tectonic Events in Luconia Shelf, Sarawak, Malaysia - Jamaludin, Siti Nur Fathiyah; Sautter, Benjamin; Pubellier, Manuel; Beg, Mirza Arshad (Frontiers in Earth Science, 2021)
Using high quality regional seismic lines, we evidence major structures resulting from successive phases of tectonic events that affected the Luconia shelf from the Upper Cretaceous to Pliocene. Each tectonic event (Classified as Event 1 to Event 3) is associated with different episodes of limestone growth in Luconia Province. The successive limestone growths are used as markers in constraining the timing and style of tectonic deformation. The poly-stage closure of the Proto South China Sea (PSCS) from the Upper Cretaceous to Lower Miocene led to the formation of compressional structures in its southern portion (South PSCS) providing elevated topography for the growth of the oldest limestone found in this area during the Upper Eocene to Lower Oligocene (Event 1). Based on contrasting seismic reflectors, morphology, and depositional patterns, the offshore Upper Eocene-Lower Oligocene limestone growth is correlated to the onshore Engkabang-Karap limestone. The southern part of Luconia was subjected to a continuous compression until the Lower Miocene at a time where the northern side of the Luconia Province was experiencing subsidence due to the rifting of the South China Sea (Event 2). The compression in the south generated elevated anticlines, triggering the growth of the Upper Oligocene to Lower Miocene limestone. By the end of the rifting event in the Lower Miocene, tectonic quiescence had enabled widespread carbonate growth in Luconia from the Middle to Upper Miocene. Regional compression due to the major uplift of Borneo hinterland (Event 3) triggered paramount clastic influx (gravity tectonics) to the offshore perturbating the limestone reef growth in Luconia. The impact of these interrelated shortening and stretching phases led to major crustal thickness variations and a prominent tilt of the Luconia platform that may highlight intricate feedbacks at the transition from compression to extension. While the southern side of the Luconia’s crustal fragment was anchored into Borneo hinterland, crustal extension in the northern region of Luconia led to a hyper-stretched crust characterized by low angle detachment faults and highly rotated blocks rising the mantle to its shallowest.